DEVELOPING AN ENGLISH LEARNING E-BOOK FOR GRADE 6 STUDENTS - Putri, Julie Abiya; Misrita, Misrita; Zulkarnain, Zulkarnain (Journal Compound: Improving the Quality of English Education, 2024)
This study developed an English learning e-book for Grade 6 students using the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model to address curriculum requirements and enhance student engagement. The e-book focused on teaching language skills related to past activities, WH questions, and future plans. Key features included audio recordings, interactive exercises, vibrant visuals, and Google Forms for instant feedback. During the implementation phase, the e-book was tested in a simulated classroom setting, revealing initial usability issues such as unclear interactive features. Based on feedback, revisions improved the design by making links and buttons more user-friendly. Subsequent testing showed significant enhancements in usability and engagement, with the e-book effectively supporting students’ learning. This research highlighted the potential of integrating multimedia and digital tools in language instruction. The e-book served as an innovative resource, demonstrating how technology can improve teaching methods, align with curriculum goals, and foster active learning among primary school students.